2013
DOI: 10.1152/ajpheart.00872.2012
|View full text |Cite
|
Sign up to set email alerts
|

Physiological cyclic strain promotes endothelial cell survival via the induction of heme oxygenase-1

Abstract: Endothelial cells (ECs) are constantly subjected to cyclic strain that arises from periodic change in vessel wall diameter as a result of pulsatile blood flow. Application of physiological levels of cyclic strain inhibits EC apoptosis; however, the underlying mechanism is not known. Since heme oxygenase-1 (HO-1) is a potent inhibitor of apoptosis, the present study investigated whether HO-1 contributes to the antiapoptotic action of cyclic strain. Administration of physiological cyclic strain (6% at 1 Hz) to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 50 publications
3
55
0
Order By: Relevance
“…In vitro, transfection with the human HO-1 gene increased blood vessel formation (24). In endothelial cells, hemodynamically relevant cyclic strain stimulated HO-1 gene expression and inhibited cell death (63). In vivo, lentiviral vectors with microRNA sequences controlled by vascular endothelium cadherin were used to study the role of lung endothelial HO-1 in mice exposed to hyperoxia (119).…”
Section: Multiple Roles Of Ho-1 In Angiogenesis and Vascular Prolifermentioning
confidence: 99%
“…In vitro, transfection with the human HO-1 gene increased blood vessel formation (24). In endothelial cells, hemodynamically relevant cyclic strain stimulated HO-1 gene expression and inhibited cell death (63). In vivo, lentiviral vectors with microRNA sequences controlled by vascular endothelium cadherin were used to study the role of lung endothelial HO-1 in mice exposed to hyperoxia (119).…”
Section: Multiple Roles Of Ho-1 In Angiogenesis and Vascular Prolifermentioning
confidence: 99%
“…Moreover, HO-1 overexpression reduces the production of ROS and attenuates the production of inflammatory cytokines, including IL-8, by activating ECs and macrophages [39,40] . Furthermore, the induction of HO-1 expression in ECs restores the endothelial integrity of injured vessels by stimulating the proliferation and migration of ECs from regions adjacent to the injured artery and by recruiting circulating endothelial progenitor cells to the site of damage [41] . Several therapeutic agents, including statins, resveratrol, rapamycin, paclitaxel, NO, aspirin, and probucol, induce HO-1 expression [32,42] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HO-1 silencing significantly abrogated the inhibitory effects of nicorandil on cyclic strain-induced IL-8 expression, suggesting that the anti-inflammatory action of nicorandil may, at least partly, be attributed to nicorandil-induced HO-1 expression as a defense mechanism. Liu et al [41] found that cyclic strain significantly inhibits cytokine-mediated EC apoptosis, and that HO-1 expression underlies this cytoprotective effect. Nevertheless, further investigation is necessary to fully characterize the association between HO-1 and IL-8 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its significance is notably wider than only haem elimination. HMOX1 is one of the most highly induced genes in cells exposed to stressful conditions, and hundreds of experiments have demonstrated that the products of HMOX1 activity are involved in the maintenance of cell homoeostasis (29). The importance of HMOX1 in cardiovascular diseases and cancer progression has been commonly accepted, particularly when considering the variability of HMOX1 in the human population, resulting from HMOX1 promoter polymorphism (30).…”
Section: Discussionmentioning
confidence: 99%